How animal ethics committees make decisions – a scoping review of empirical studies - Aoife Milford; Eva De Clercq; Edwin Louis-Maerten; Lester D. Geneviève; Bernice S. Elger (PLoS ONE, 2025)
Objectives The aim of the scoping review is to explore the decision-making process for the evaluation of animal research proposals within Animal Ethics Committees (AEC) and Institutional Animal Care and Use Committees (IACUC), and to critically summarize the available empirical literature on the different factors influencing, or likely to influence, decision-making by AECs when evaluating animal research proposals. Methods A systematic search of empirical literature published between 01.12.2012 and 03.06.2024 in PubMed, Scopus, and Web of Science, was performed. Results Twelve papers were included in the final results, four of which were quantitative, five qualitative, and three were mixed methods. Qualitative content analysis revealed deficits in the assessment of the 3Rs (Replacement, Reduction or Refinement) or the weighing of harms and benefits. Factors related to the review process, applicants, and committees were found to influence this process. Conclusion The findings prompt pragmatic strategies to improve the decision making process of Animal ethics committees. Registration The protocol for this review was registered with Open Science Framework (OSF) with the following DOI: https://doi.org/10.17605/OSF.IO/GZJMB